1992
DOI: 10.1128/aac.36.8.1785
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of streptomycin and 11 oral antimicrobial agents against clinical isolates of Klebsiella rhinoscleromatis

Abstract: We tested in vitro the activities of streptomycin and tetracycline-antibiotics that have long been used to treat rhinoscleroma-as well as several newer oral agents by using 23 isolates of the causative organism KlebsieUla rhinosckeromatis. All isolates were inhibited by clinically achievable concentrations of trimethoprim-sulfamethoxazole, amoxicillin-clavulanate, chloramphenicol, ciprofloxacin, cephalexin, cefuroxime, and cefpodoxime.Klebsiella rhinoscleromatis causes rhinoscleroma, a chronic granulomatous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…All taxa were naturally resistant or intermediate to amoxicillin and ticarcillin, but sensitive to amoxicillin/clavulanate and cephalosporins. These ®ndings are consistent with data of Perkins et al [26] and Podschun and Ullmann [10]. Because of higher MIC values to all â-lactam agents it is likely that the strains included in the latter study showed an increased â-lactamase expression compared with strains in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…All taxa were naturally resistant or intermediate to amoxicillin and ticarcillin, but sensitive to amoxicillin/clavulanate and cephalosporins. These ®ndings are consistent with data of Perkins et al [26] and Podschun and Ullmann [10]. Because of higher MIC values to all â-lactam agents it is likely that the strains included in the latter study showed an increased â-lactamase expression compared with strains in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Klebsiella rhinoscleromatis is normally sensitive to the majority of antibiotics that are active on Gram-negative bacteria except for penicillin, ampicillin and sulfonamide [14], with ciprofloxacin and rifampin the most effective antimicrobials [15]; in terms of efficacy/cost, the association of trimethoprim-sulfamethoxazole is the best compromise [7]. Botelho-Nevers et al .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, these bacteria are inhibited by clinically achievable concentrations of amoxicillin -clavulanate, chloramphenicol, trimethoprim -sulfamethoxazole, cephalosporins, streptomycin, tetracyclines and ciprofloxacin 32 . However, in vivo, antibiotics with demonstrated efficacy are streptomycin, doxycycline, tetracycline, rifampicin, second-and third-generation cephalosporin, sulfonamides, clofazimine, ciprofloxacin 11 and ofloxacin 31 .…”
Section: Discussionmentioning
confidence: 99%